Optimization and Simulation of Accounting Information Practice Model Assisted by Discrete Dynamic Events. (21st May 2022) - Han, Yusheng
Abstract : The performance function expressed by the expected value of the discrete event dynamic system usually does not have a closed analytical expression, so it can only be estimated by the Monte-Carlo method. The inherent limitations of the Monte-Carlo method (low simulation efficiency) and the complexity of the system bring a lot to the simulation optimization problem. A huge challenge has come. A reasonable combination of mathematical methods and computer simulation technology is an important direction to study the optimal design of DESD. On the basis of linear systems on maximal algebras, this article studies a class of multimodel systems on maximal algebras. This article presents a non-Markov DEDS time-synchronized parallel simulation algorithm and proves that the common random number method can maximize the simulation efficiency of an existing event-synchronized algorithm. We take advantage of the inherent parallelism of genetic algorithm, and combine the idea of parallel simulation and DEDS order optimization to give an optimization algorithm for discrete parameter space DEDS. This article discusses the relationship between ultimate control, internal control, and accounting information quality. This article analyzes the relationship between ultimate control right, internal control, and accounting information quality. We use the manipulated accruals calculated by the modified Jones model and the earnings response coefficient of the earnings-return model to measure the quality of accounting information, and analyze the impact of the ultimate control ratio and internal control level on the quality of accounting information. Based on the difference in the nature of the controller and the ratio of ultimate control rights, this article examines the difference in the effect of internal control on the quality of accounting information in companies with high and low ratios of ultimate control rights. The robustness tests of the two accounting information measurement models are carried out, respectively, and the results obtained are basically consistent with the empirical research conclusions. The situation is the most important to its own development. Among them, the asset turnover rate has a greater effect on the early warning of corporate financial crisis, and the status of the current asset turnover rate and the total asset turnover rate in the financial early warning is also crucial. This article studies the correlation between the overall level of internal control and the quality of accounting information, avoiding the one-sidedness caused by using a single index to measure the level of internal control.